Leveraging inter-organizational networks to scale up a sepsis recovery program: results from an application of the Making Optimal Decisions for Intervention Flexibility during Implementation (MODIFI) method - Cheyenne R. Wagi; Marc A. Kowalkowski; Stephanie P. Taylor; Aliza Randazzo; Asha Ganesan; Amit Khanal; Sarah A. Birken (Implementation Science Communications)
Abstract Background Nearly two million adults in the United States are hospitalized with sepsis yearly, with survivors facing complications that result in high rates of hospital readmission and mortality after discharge. We demonstrated improved outcomes following discharge among sepsis survivors who participated in the Sepsis Transition And Recovery (STAR) program; however, important differences among hospitals require STAR’s adaptation to facilitate its implementation and ensure its effectiveness in new settings. Purpose The purpose of this study was to adapt STAR to hospitals with diverse characteristics. Methods We used the Making Optimal Decisions for Intervention Flexibility during Implementation (MODIFI) approach. We identified STAR core functions (i.e., effectiveness-driving features) using semi-structured key informant interviews (n = 7). We identified adaptations using semi-structured interviews with clinicians and leaders with expertise and oversight of resources related to transitions of care after sepsis hospitalization (n = 7) from four hospitals that systematically differed from the hospitals in which we originally found STAR to be effective. Results Network theory, which proposes that performance improves with more efficient flow of information within and across hospitals, underlays STAR’s eleven core functions. Adaptation included specific points-of-contact, communication preferences, and methods for achieving buy-in. We used proposed adaptations to tailor STAR protocols to each hospital. Conclusions We used MODIFI, a state-of-the-science method, to adapt a program that was effective in promoting transition and recovery in sepsis survivors to facilitate its scale-up to diverse hospitals. Future studies will assess STAR’s implementation and effectiveness in diverse hospitals.